Ivory Coast: aquaculture expands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Eight provinces in the Ivory Coast practise aquaculture Aboisso, Bandoukou, Bouake, Daloa, Gagnoa, Korhogo, Man and Touba. The number of fish farms has risen from nine in 1980 (136 ponds) to 946 in 1984. Two-thirds of these are nationally owned...